Intraspecific phylogeny and genomic resources development for an important medical plant Dioscorea nipponica, based on low-coverage whole genome sequencing data - Hu, Ke; Chen, Min; Li, Pan; Sun, Xiaoqin; Lu, Ruisen (Frontiers in Plant Science, 2023)
Dioscorea nipponica Makino, a perennial twining herb with medicinal importance, has a disjunctive distribution in the Sino-Japanese Floristic Region. It has a long history in traditional Chinese medicine, with demonstrated efficacy against various health conditions. However, the limited genomic data and knowledge of genetic variation have hindered its comprehensive exploration, utilization and conservation. In this study, we undertook low-coverage whole genome sequencing of diverse D. nipponica accessions to develop both plastome (including whole plastome sequences, plastome-derived SSRs and plastome-divergent hotspots) and nuclear genomic resources (including polymorphic nuclear SSRs and single-copy nuclear genes), as well as elucidate the intraspecific phylogeny of this species. Our research revealed 639 plastome-derived SSRs and highlighted six key mutational hotspots (namely CDS ycf1, IGS trnL-rpl32, IGS trnE-trnT, IGS rps16-trnQ, Intron 1 of clpP, and Intron trnG) within these accessions. Besides, three IGS regions (i.e., ndhD-cssA, trnL-rpl32, trnD-trnY), and the intron rps16 were identified as potential markers for distinguishing D. nipponica from its closely related species. In parallel, we successfully developed 988 high-quality candidate polymorphic nuclear SSRs and identified 17 single-copy nuclear genes for D. nipponica, all of which empower us to conduct in-depth investigations into phylogenetics and population genetics of this species. Although our phylogenetic analyses, based on plastome sequences and single-copy nuclear genes revealed cytonuclear discordance within D. nipponica, both findings challenged the current subspecies classification. In summary, this study developed a wealth of genomic resources for D. nipponica and enhanced our understanding of the intraspecific phylogeny of this species, offering valuable insights that can be instrumental in the conservation and strategic utilization of this economically significant plant.